Isolation And Characterization Of A Full-Length Knotted Gene From Oil Palm (Elaeis Guineensis Jacq.) - Che Mohd Zain, Che Radziah (2005)
The oil palm is one of the most important commercial oil crops that produces high quality of oil and with it comes an increasing global demand for this crop. The clonal oil palm produced by tissue culture technique provides an opportunity to expand productivity in order to fulfill the vast demand. However a number of reports have documented the occurrence of abnormalities in clonal oil palm such as vegetative abnormalities of tissue-cultured plantlets and also abnormalities of flowers. There has been no fundamental understanding of the cause of these abnormalities. Since the tissues and organs of plants originate fiom apical meristerns, it is worthwhile to study the molecular mechanism underlying organ morphogenesis k m this undifferentiated meristem cells. Within the past several years, there are several lines of evidence indicating that the homeobox genes control pattern formation and morphological structure determinations in multicellular eukaryotes including plants. In this study, Knotted homeobox gene was identified and isolated in order to develop an understanding of the function of this gene during oil palm development. In order to isolate the fiill-length Knotted homcobox gene from oil palm, an oil palm (Elaeis guineensis Jacq.) suspension culture cDNA library of was screened with a partial cDNA clone (putative oil palm Knotted gene). From the screening, the full-length of oil palm Knotted homeobox gene was isolated and designated as oil galm Knotted homeobox gene (OPKNI). This thesis describes the first homeobox gene isolated from oil palm. Sequence analysis showed that OPKNl belongs to the class-1 Knotted gene family. Expression study by semiquantitative RT-PCR, northern blot as well as in situ hybridization analyses proved that OPKNl gene was expressed in both vegetative and floral meristems suggesting a function in both phases of development. Based on semi-quantitative RT-PCR analyses, OPKNl was shown to be expressed in all meristem-based tissues including shoot apex, both male and female floral meristems, embryogenic callus, and suspension cell cultures. This seems to indicate that OPKNI may play role in meristem organization and later in morphogenesis processes. This can be supported by the presence of OPKNl transcript in leaf prirnordia suggesting that it may play roles in the development of pimate leaf in oil palm. The presence of OPKNl throughout the flower development in both normal and abnormal flowers also indicates that the gene is active during floral development, suggesting a function in floral morphogenesis. Furthermore, the differences in temporal and spatial expression of OPKNl in different stages and type of meristem tissues may cause error in organ determination. iii